“Resistenza senza la resistenza”. The History and the Invention in the texts of Lalla Romano - La Monaca, Donatella (ItaliAMO: Promotion of Italian Studies in the Academic and Non-Academic Environment, 2023)
“Resistance without Resistance, an intimist Resistance, the only one possible if one does not have Fenoglio’s epic dimension” wrote Lalla Romano in 1987. On the thrust of this consideration, we will focus on the relationship between history and invention and its thematic-stylistic declination in some of the writer’s most compromised narrative and nonfiction pages with post-World War II history. It will reflect on how the web of contaminations becomes thicker and the border between private chronicle and public history more fluid in a narrative’ deliberately alien to any “celebratory rhetoric”.